Effects of Genotype and Sex on Carcass Traits, Myosin Heavy Chain Isoforms and Meat Characteristics of Pigs - Chaosap, Chanporn; Buajoom, Wuttikorn; Pothising, Numfon; Kongtasorn, Chananya; Adeyemi, Kazeem D. (My University, 2025)
This study investigated the effects of genotype and sex on carcass traits, myosin heavy chain (MyHC) isoforms, and meat quality in pigs raised under Thai commercial conditions. Fifty pigs (25 barrows and 25 gilts) from five genotypes—purebred Duroc (D), LWLR1 (Large White_old × Landrace_old), LWLR2 (Large White_new × Landrace_new), DLWLR1 (Duroc × LWLR1), and DLWLR2 (Duroc × LWLR2)—were slaughtered at ~110 kg body weight. LWLR1 is traditional maternal line, whereas LWLR2 is a newly selected line for higher intramuscular fat (IMF). Significant genotype × sex interactions were observed for dressing percentage, carcass length, bone percentage, purge loss, pH24, and L* (lightness) (p < 0.05). The Longissimus lumborum (LL) muscle of Duroc pigs showed the lowest pH45 and shear force but highest IMF, whereas LWLR1 pigs exhibited higher crude protein, polyunsaturated fatty acids, and flavor-enhancing nucleotides. The LL muscle of LWLR2 and DLWLR2 pigs showed greater expression of MyHC I and IIA, as well as calpain 1 (CAPN1), calpain 2 (CAPN2), and calpastatin (CAST) genes. In contrast, Duroc pigs had the highest MyHC IIX and lowest IIB expression, opposite to patterns in LWLR1 and DLWLR1. Principal component analysis revealed distinct genotype-based clustering, emphasizing the influence of maternal lineage on pork quality and offering valuable insights for genetic selection strategies.
Keywords: CAPN1; inosine monophosphate; intramuscular fat; purge loss; shear force